Die Probleme der Landwirtschaft in Polen 1989-2003 [The problems of agriculture in Poland 1989-2003] - Janicki, Tadeusz (Studia Historiae Oeconomicae, 2009)
In the years 1989-2003, Poland's political, economic and social life underwent fundamental changes, which are usually referred to as the post-socialist system transformation. The aim of the activities undertaken at that time was the transition from real socialism to democracy and a market economy. Three principles were adopted as the basis for the transition: liberalization, deregulation and privatization. The political upheaval of 1989 also marked the beginning of a new era in the history of Polish agriculture. Once again (after the 19th century and the interwar period), processes of adaptation to the system of the capitalist market economy began.